2016
DOI: 10.1212/wnl.0000000000003253
|View full text |Cite
|
Sign up to set email alerts
|

Deconstructing tolerance with clobazam

Abstract: Objective:To evaluate potential development of tolerance to adjunctive clobazam in patients with Lennox-Gastaut syndrome.Methods:Eligible patients enrolled in open-label extension study OV-1004, which continued until clobazam was commercially available in the United States or for a maximum of 2 years outside the United States. Enrolled patients started at 0.5 mg·kg−1·d−1 clobazam, not to exceed 40 mg/d. After 48 hours, dosages could be adjusted up to 2.0 mg·kg−1·d−1 (maximum 80 mg/d) on the basis of efficacy a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…21 A later open-label study defined tolerance as a dosage increase of 40% plus loss of response and found a rate of tolerance of 12%. 6 We broadly considered either a relapse in seizure frequency or dose increase to represent tolerance; our study found development of tolerance at 1 year in approximately one-fourth of patients, a lower rate than most prior studies, and a rate of discontinuation that is highest in the first month after initiation of clobazam.…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…21 A later open-label study defined tolerance as a dosage increase of 40% plus loss of response and found a rate of tolerance of 12%. 6 We broadly considered either a relapse in seizure frequency or dose increase to represent tolerance; our study found development of tolerance at 1 year in approximately one-fourth of patients, a lower rate than most prior studies, and a rate of discontinuation that is highest in the first month after initiation of clobazam.…”
Section: Discussionmentioning
confidence: 79%
“…3,4 As the a 1 receptor is largely responsible for sedating effects of benzodiazepines, clobazam is therefore less sedating; this increased specificity has also been proposed to contribute to the lesser degree of tolerance seen with clobazam than with other benzodiazepines. 5,6 Clobazam was approved by the United States Food and Drug Administration (FDA) in 2011 for treatment of Lennox-Gastaut syndrome (LGS). 7 Since that time, there has been increasing off-label use of clobazam in adults with refractory epilepsy and anecdotal evidence that it may be more effective than other AEDs.…”
mentioning
confidence: 99%
“…Although tolerance is typically associated with prolonged treatment and high doses of antiseizure drugs [2], it may be associated with a number of other factors, key of which are pharmacokinetic and pharmacodynamic properties of the drug [1,2], as well as other factors that may occur acutely. Tolerance may also vary with seizure type, even with the same agent, as illustrated by studies of clobazam showing higher levels of tolerance in patients with temporal lobe epilepsy (27% at 1 year [3]) compared with Lennox-Gastaut syndrome (12% at 2 years [4]). Those studies defined tolerance as the development of partial or complete loss of therapeutic effectiveness [3] or a dosage increase !40% plus loss of response [4].…”
Section: Introductionmentioning
confidence: 99%
“…Tolerance may also vary with seizure type, even with the same agent, as illustrated by studies of clobazam showing higher levels of tolerance in patients with temporal lobe epilepsy (27% at 1 year [3]) compared with Lennox-Gastaut syndrome (12% at 2 years [4]). Those studies defined tolerance as the development of partial or complete loss of therapeutic effectiveness [3] or a dosage increase !40% plus loss of response [4].…”
Section: Introductionmentioning
confidence: 99%